Experimental Study on Physical-Mechanical Properties of Expansive Soil Improved by Multiple Admixtures - Binhui Ma; Kai Cai; Xing Zeng; Zhuo Li; Zhiyong Hu; Qiunan Chen; Chengbin He; Bingchu Chen; Xiaocheng Huang (Advances in Civil Engineering)
The treatment of expansive soil is always a difficult problem in engineering. Using coal gangue, fly ash, and other solid waste to treat expansive soil has gradually become a new way of energy saving and environmental protection. Most of the existing studies focus on using one or two kinds of admixtures to improve expansive soil, but there are few studies on improving expansive soil with multiple admixtures. In this paper, the expansion and shrinkage deformation and strength characteristics of expansive soil modified by coal gangue, fly ash, and lime are studied experimentally. Nine groups of different mixing schemes were designed through orthogonal tests, and the physical and mechanical properties of the improved expansive soil under different mixing ratios were tested. The sensitivity analysis of the test results was carried out to study the effect of each admixture on the improved expansive soil under different mixing ratios, and the optimal mix ratio under different conditions was obtained. The optimal mix ratio is 8% for coal gangue, 11% for fly ash, and 6% for lime. Further scanning electron microscopy (SEM) tests were carried out to analyze the microstructure of the improved expansive soil and explore the improvement mechanism of the multiadmixture. The results show that the optimal moisture content and the maximum dry density of the expansive soil with ash are decreased, and the properties of liquid plastic limit, free expansion rate, shear strength, and unconfined compressive strength of the expansive soil are improved obviously. Through the analysis of the comprehensive balance method, it is found that the content of lime has the greatest influence on the improvement effect of expansive soil, followed by that of coal gangue, and the least is that of fly ash. SEM structure analysis reveals that the particles of improved expansive soil are mainly aggregates, the soil structure is dense, particle agglomeration increases, and the overall structure is stronger. The research results can provide reference for the improvement of expansive soil with various admixtures and the resource utilization of coal gangue, fly ash, and other solid wastes.